Case Report: Safety and efficacy assessment of teclistamab in relapsed/refractory amyloidosis: a case study - Chen, Zhe; Zhang, Zhijian; Yu, Jieni; Fu, Leihua; Fu, Jiaping; Feng, Weiying (Frontiers in Oncology, 2025)
Systemic light chain amyloidosis (AL) is an uncommon disorder of clonal plasma cells, marked by the creation of amyloid-forming immunoglobulin light chains that result in amyloid fibril formation and deposition, causing dysfunction in multiple organs. There is no established treatment protocol for patients with relapsed or refractory AL. Teclistamab is a bispecific antibody targeting B-cell maturation antigen (BCMA) and is approved for treating relapsed or refractory multiple myeloma (MM). The objective of our study was to report real-world data on the safety and efficacy of teclistamab in patients with relapsed/refractory AL.